THE ADVANTAGES OF FREE FULL-LAYER SKIN GRAFTING IN THE ELIMINATION OF POST-BURN CONTRACTURES OF THE SHOULDER AND ELBOW JOINTS IN CHILDREN. - Ketmonov , Alisher; Yulchiyev , Karimjon; Abdurakhmanov, Farrux (International Journal of Scientific Pediatrics, 2023)
In children, the frequency of thermal burns is higher than in adults. Of course, it depends on the level of inattention of children. The development of science and technology is steadily increasing the number of children suffering from thermal burns. Although the development of medicine reduces the mortality of children suffering from severe thermal burns, it cannot solve the problems associated with the increase in the number of disabilities caused by post-burn complications. Post-burn complications develop in 20-22% of children with thermal burns. Purpose of work: to improve the results of elimination of cicatricial contractures of the shoulder and elbow joints in children. Materials and methods of research: In the article in 2019-2022. the postoperative results of 72 children with complications caused by burns of the shoulder and elbow joints in the Department of Maxillofacial and Plastic Surgery of the Children’s Multidisciplinary Medical Center of Andijan region are presented. studied. Results and discussion: 25 children were treated with traditional skin plasty using a dermatome for post-burn cicatricial contractures of the shoulder and elbow joints. Results were discussed between 3 and 6 months. Good functional and cosmetic results were achieved in 21 (84%) patients. 47 pediatric patients underwent skin resection with a free flap for post-burn cicatricial contractures of the shoulder and elbow joints, good functional and cosmetic results were achieved in 45 (96%) patients.